IMPLEMENTASI SHARABLE CONTENT OBJECT REFERENCE MODEL DALAM LEARNING MANAGEMENT SYSTEM (STUDI KASUS PADA AKMI BATURAJA) - Pujianto Pujianto; Ahmad Ashari (Seminar Nasional Informatika (SEMNASIF), 2012)
To develop e-learning system in order to become a standard SCORM (sharable Content Object Reference Model) system, necessary improvement on its content and environment are needed. Many e-learning systems owned by the institutions have non SCORM standard materials for learners. This study aimed to build a SCORM standard e-learning system especially on the content so that can be integrated into a various LMS (Learning Management Systems) or e-learning system that supports SCORM. The method used in this research is modified waterfall thats developed by Winston Royce. To create some content on the courses, transform them into SCORM standards, integrate the contents on e-learning systems and test them. SCORM Standard content was created using open source tools. Content that has been made in the store in the SCORM base content. Testing was done by the lecturer by importing the packages content that are already in SCORM standards.